Hedging of Price Risks on Petrochemicals. Case of Retal Industries Ltd. - Potapov, Denis (2016)
This thesis presents the hedging theory and its application in order to create an optimal hedging strategy for Retal Industries Ltd. on the PET market. Through this work the hedging theory is tested and assessed basing on its relevance for actual business needs.